Pojęcie stylizacji jako narzędzia opisu utworów literackich - Wojtak, Maria (Stylistyka, 1994)
The authoress formulates stylization as a style-creating process which depends on the approving or polemic reference to the non-literary patterns of language behaviour. She describes both the universal stylization procedures, and peculiar rules of the game with a stylization pattern. The authoress shows, on the basis of analysis of a work from the roguish circle of literature, that the description of stylization can be not only the foundation of a stylistic characteristic of the text, but can also make its interpretation easier.